Management of a chronic radiation necrosis wound with lyopreserved placental membrane containing viable cells - Matthew J. Regulski (Clinical Case Reports, 2019)
Key Clinical Message This case report describes management of a chronic radiation wound in a patient with multiple comorbidities using a lyopreserved placental membrane containing viable cells (vLPM). Positive outcomes suggest that vLPM provides a good conservative management option for patients with compromised wound healing due to radiation and comorbidities.